Performance of black pepper (Piper nigrum L., var. Panniyur-1) trained on different shade trees as live standards - ANKEGOWDA, V S KORIKANTHIMATH, S J (Journal of Spices and Aromatic Crops, 1999)
Thepraductivity of black pepper (Piper nigrum L.) mainly depends on moisture content of soil and light availability. Mathai & Chandy (1988) reported that low productivity at the lower parts of the canopy in black pepper is due to low light availability to the vines at this region.